The Biochemical Pattern of Liver Function Tests in Adult Patients of Diabetes and the Association with Hypoglycemic Medications - Nageen, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the biochemical pattern of liver function tests in adult patients of diabetes and the association with hypoglycemic medications. Study Design: Cross-sectional study. Place and Duration of Study: Creek General Hospital, Karachi Pakistan, from Jun 2021 to Sep 2021. Methodology: Two sixty patients were enrolled through consecutive non-probability sampling. Adult patients with diagnosed Type 2 diabetes mellitus were included in the study. While Type 1 diabetes patients, pregnant subjects, and people with diabetes with any other systemic disease or on any other non-diabetic medications or any history of drug abuse were excluded from the study. Results: Raised Alanine transaminase levels were seen in 193 (74%) patients, a high Alkaline Phosphatase in 208 (80%) and a high Aspartate Aminotransferase in 202 (77%) patients. Liver markers were higher in the middle age group, females, hypertensive, and with abdominal obesity. There was no association between glycemic control and the duration of diabetes. The number of subjects having raised ALT and ALP was higher in those taking oral hypoglycemic and lower in those with insulin. Conclusion: The liver markers are raised in patients with diabetes and can be the predictors of future hepatotoxicity.